Immunochemical Properties of Anti-Cord Factor Antibody - Kato, Masahiko (1973)
Sera of man and animals infected with tubercle bacilli were tested for precipitating antibody to trehalose-6, 6′-dimycolate (cord factor) of Mycobacterium tuberculosis. None of the sera of mice and rabbits infected with M. tuberculosis H37Rv reacted with cord factor, whereas the sera of animals vaccinated with cord factor-methylated bovine serum albumin complex demonstrated a precipitin reaction with cord factor. Antibody against cord factor was not detected in the sera of cases of active, convalescent, and pneumonectomized human tuberculosis, indicating that the anti-cord factor antibody is not associated with tuberculous infection in man and animals. Precipitin activity against cord factor was localized in 19S macroglobulin (immunoglobulin M) fraction of the serum of rabbits vaccinated with cord factor-methylated bovine serum albumin complex. Analytical gel filtration and immunodiffusion studies indicated that the anti-cord factor precipitin dissociated from the cord factor-antibody complex is an immunoglobulin M antibody.